Assessment of Temperature Effects in Interior Orientation Parameters Calibration of Optoelectronic Devices - M. A. Starasotnikau (Приборы и методы измерений)
A digital micromirror device (DMD) micromirrors periodic spatial structure is a measuring scale in interior orientation parameters calibration of optoelectronic devices problems, when using a DMD as a testobject. It is important that DMD micromirrors periodic spatial structure remains constant. Change in a DMD micromirrors spatial structure may occur due to heating. In addition to heating a DMD, an optoelectronic device photodetector is also subject to heating and, accordingly, change in its spatial structure. It is necessary to estimate change in a spatial structure of DMD micromirrors and an optoelectronic device photodetector.A DMD micromirrors spatial drift and a DMD micromirrors spatial drift together with a digital camera photodetector pixels spatial drift for operation 4 h are analyzed. The drift analysis consisted in the points array position assessing formed by a DMD and projected onto a digital camera. When analyzing only a DMD micromirrors drift, a digital camera was turned on only for shooting time for exclude digital camera influence. A digital camera did not have time to significantly heat up, during this time. After a digital camera it cooled to a room temperature.Average drift of all DMD micromirrors determines the accuracy of interior orientation parameters calibration of optoelectronic devices using a DMD in time. Maximum drift of all micromirrors after switching on is observed. Minimum DMD warm-up time is 60 min for average drift of all micromirrors less than 1 μm is necessary. Minimum DMD warm-up time is 120 min when using a DMD together with a digital camera is necessary.A DMD expansion uniformity determines the accuracy of interior orientation parameters calibration of optoelectronic devices using a DMD, because irregular expansion disturbs micromirrors periodicity. The average change in distance of neighboring points is less than 0.1 μm for every 20 min.Thus, a DMD can be used as a test-object in interior orientation parameters calibration of optoelectronic devices. The results can be used as compensation coefficients of change in DMD micromirrors spatial structure due to temperature effects during operation, if more accurate are necessary.